SIMULASI SISTEM DETEKSI PENYUSUP DALAM JARINGAN KOMPUTER BERBASIS WEB INTERFACE SERTA PENCEGAHAN UNTUK MENINGKATKAN KEAMANAN - Prihasmoro, Sukma Ageng; Rachamawati, Rr.Yuliana; Fatkhiyah, Erfanti (Jurnal Jarkom, 2015)
ABSTRACT            Network security is a matter that needs to be given special attention, because infiltration often occurs with a variety of purposes. Intrusion detection systems (IDS) is a method of network security by detecting intrusion and provide output results in the form of alerts that can be known through the web. To implement the various components of the detection system is needed in order to maximize performance. In this study, the application is used as a detection system Snort attack. Basic Analysis and Security System (BASE) is used as a web interface. Log storage media attacks using MySQL. Fields marked with an ICMP protocol detection system ie, TCP and UDP. To follow up, use iptables and portsentry in the IP address blocking intruders. Attacks that occur can be analyzed using BASE, this application can indicate the type of attacks carried out and can see the span of attack for several months. By analyzing the types of attacks that occur, can help administrators reinforce the gap. Keywords : IDS, intruder, network security